Isoprene emission protects photosynthesis but reduces plant productivity during drought in transgenic tobacco (Nicotiana tabacum) plants. Issue 1 (17th September 2013) - Ryan, Annette C.; Hewitt, C. Nicholas; Possell, Malcolm; Vickers, Claudia E.; Purnell, Anna; Mullineaux, Philip M.; Davies, William J.; Dodd, Ian C.
Summary Isoprene protects the photosynthetic apparatus of isoprene‐emitting plants from oxidative stress. The role of isoprene in the response of plants to drought is less clear. Water was withheld from transgenic isoprene‐emitting and non‐emitting tobacco (Nicotiana tabacum) plants, to examine: the response of isoprene emission to plant water deficit; a possible relationship between concentrations of the drought‐induced phytohormone abscisic acid (ABA) and isoprene; and whether isoprene affected foliar reactive oxygen species (ROS) and lipid peroxidation levels. Isoprene emission did not affect whole‐plant water use, foliar ABA concentration or leaf water potential under water deficit. Compared with well‐watered controls, droughted non‐emitting plants significantly increased ROS content (31–46%) and lipid peroxidation (30–47%), concomitant with decreased operating and maximum efficiencies of photosystem II photochemistry and lower leaf and whole‐plant water use efficiency (WUE). Droughted isoprene‐emitting plants showed no increase in ROS content or lipid peroxidation relative to well‐watered controls, despite isoprene emission decreasing before leaf wilting. Although isoprene emission protected the photosynthetic apparatus and enhanced leaf and whole‐plant WUE, non‐emitting plants had 8–24% more biomass under drought, implying that isoprene emission incurred a yield penalty.